Nucleophilic Addition of Alkanenitriles to Aldehydes via N-Silyl Ketene Imines Generated In Situ - Yoshimura, Fumihiko; Saito, Hiroki; Abe, Taiki; Tanino, Keiji (Synlett, 2017)
Upon treatment with triisopropylsilyl trifluoromethanesulfonate and 2,2,6,6-tetramethylpiperidine, alkanenitriles undergo direct addition to aldehydes under mild non-basic neutral conditions to provide triisopropylsilyl ethers of β-hydroxy nitriles in good yield. The reaction proceeds through generation of an N-silyl ketene imine intermediate in situ from the alkanenitrile followed by nucleophilic addition of the intermediate to the aldehyde.
Keywords: nitriles; nitrile aldol reaction; nucleophilic addition; N-silyl ketene imines; aldehydes